The Function of a Zoonym in English and Russian Phraseology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article will consider the problem of similarities and differences between phraseological units such as function of zoonyms in English and Russian, based on the criteria of "moral qualities". Zoonyms and stable expressions are an inorganic component of language culture and interpersonal communication, an important feature in terms of the national characteristics of the language under study and at the same time socio-cultural phenomena common to all peoples.Therefore, when learning a foreign language, students should pay attention to mastering this component of foreign language culture, which gives the language a special color and national flavor. The correct use of phraseological units for students in the practical application of the acquired knowledge gives this knowledge a special depth and versatility. A comparative analysis of the phraseological units of the studied foreign and native languages is also useful, which helps not only to expand the student's worldview, but also to better consolidate the material.